2020
DOI: 10.1177/0885412220944919
|View full text |Cite
|
Sign up to set email alerts
|

One and the Same? A Systematic Literature Review of Residential Property Investor Types

Abstract: This article presents a systematic literature review on residential property investor types in selected social science disciplines and critically evaluates the status quo of academic engagement within this diverse group of property market actors. A recurring critique in recent years has been the minimal acknowledgment of investor heterogeneity particularly in relation to urban development and the financialization of housing. Yet, to date, there is no systematic evidence supporting these contentions. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 133 publications
0
30
0
Order By: Relevance
“…A systematic literature review on residential investor types revealed that investors in these disciplines are rarely thoroughly described, that categorisations and theorisations of investor types are scarce, and that generalisations are often made on the basis of simple divisions such as large and small, or local and global, investors (Özogul and Taşan-Kok, 2020). More technical differentiations on the type of investment finance, ownership composition and investment strategies can be found in the field of economics (Özogul and Taşan-Kok, 2020). Even financialisation literature tends to treat investors as a uniform actor group purely following 'economic calculations and rationalities' (Raco et al, 2019(Raco et al, : 1069.…”
Section: An Actor-centred Approach To Urban Property Investment Market Shiftsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic literature review on residential investor types revealed that investors in these disciplines are rarely thoroughly described, that categorisations and theorisations of investor types are scarce, and that generalisations are often made on the basis of simple divisions such as large and small, or local and global, investors (Özogul and Taşan-Kok, 2020). More technical differentiations on the type of investment finance, ownership composition and investment strategies can be found in the field of economics (Özogul and Taşan-Kok, 2020). Even financialisation literature tends to treat investors as a uniform actor group purely following 'economic calculations and rationalities' (Raco et al, 2019(Raco et al, : 1069.…”
Section: An Actor-centred Approach To Urban Property Investment Market Shiftsmentioning
confidence: 99%
“…To create such a framework, we start from the premise that investors are complex and multifaceted entities that may exhibit diverse behaviours, which can be far from standardised or calculable. The first three dimensions that we selected for our framework to define an investor (see Figure 1 legend) stem from the extensive literature review that we conducted elsewhere (Özogul and Taşan-Kok, 2020). In this systematic review, we methodically searched for residential investor types and differentiations addressed in existing urban studies, urban and regional planning, geography, public administration, sociology and economics literature to counter the limited in-depth scholarly engagement with investors from an interdisciplinary perspective.…”
Section: An Actor-centred Approach To Urban Property Investment Market Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large and varied literature on financialisation illustrates the spread of calculative practices and transaction mechanisms influencing and influenced by a growing diversity of players (for comprehensive literature reviews see Özogul and Tasan-Kok, 2020; Pani and Holman, 2014; Pike and Pollard, 2010). One underlying assumption that cuts across this diverse body of work is that the advance of financialisation is heavily reliant on quantitative measurements and technologies.…”
Section: Understanding(s) Of Real Property Managementmentioning
confidence: 99%
“…The wider literature discerns different perspectives on actual property development processes, such as from political economy, Marxist or institutional stances (see Drane, 2013 for a useful overview). Institutional perspectives prove most beneficial to counter dichotomous thinking and the widespread generalisations of property industry actors in planning studies (Özogul & Tasan-Kok, 2020;Campbell et al, 2014;Adams and Tiesdell 2012). They tend to approach property as a 'bundle of relations' capturing the intricate interplay between public and private sector actors (Blomley, 2017;Fainstein, 2008).…”
Section: Planning Property and Learning: Institutional Change Througmentioning
confidence: 99%